Энциклопедия вязания - Максимова Маргарита Васильевна (Легпромбытиздат, 1993)
Экземпляры: ф.12 (1993) / Инвентарный номер: 36874 / Цена: / Сис.шифр: 37.248 / Авт.знак: М17 / ГРНТИ: 75.35 / ББК: 37.248